BIMBINGAN KONSELING ISLAM DALAM MENGEMBANGKAN RELIGIOUS PRACTICE DI PONDOK PESANTREN WARIA AL-FATAH YOGYAKARTA - Agus Riyadi (Sociocouns: Journal of Islamic Guidance and Counseling, 2022)
This study aims to describe Islamic counseling guidance in developing the counselee's religious practice at the Waria al-Fatah Islamic boarding school, by using field research in finding sources relevant to the research, and using in-depth interview techniques, participant observation, and documentation to explore data. existing data, and using source triangulation and technical triangulation to validate existing data, and using John W. Creswell's spiral data analysis model to analyze the data obtained in the field. The results showed that; (1) Islamic counseling guidance has a positive influence on the counselee on aspects of religious practice; (2) Islamic counseling guidance cannot be said to be effective, because the service does not have a systematic and well-structured procedure and service management as Islamic counseling guidance is carried out in general; (3) the supporting and hindering factors of service consist of several things, namely; the existence of the counselee's motivation, the counselor's skills in building an atmosphere, the existence of additional religious programs, and the existence of adequate facilities for feelings, while for the inhibiting factors themselves, namely; related to the negative stereotypes and stigma of the majority of the community, lack of service time, and lack of human resources at the Waria al-Fatah Islamic boarding school which focuses on Islamic counseling guidance for transgender people.